Sound management strategies in swiftlet ranching from Southern Thailand - NANTACHAI PONGPATTANANURAK; SANGSAN PHUMSATHAN; TANIT SOMLEEWONG; PHRUT RASRI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Pongpattananurak N, Phumsathan S, Somleewong T, Rasri P. 2023. Sound management strategies in swiftlet ranching: An experiment from Southern Thailand. Biodiversitas 24: 6218-6228. Edible-nest swiftlets are well-known for the medicinal properties of their nests. With the global demand, swiftlet ranching has emerged as a vital industry. Swiftlet houses employ acoustic stimuli to entice wild swiftlets. However, the use of loud acoustic stimuli in swiftlet houses has inadvertently led to sound pollution in urban areas. This study investigates the interplay of acoustic stimuli, loudness, and environmental factors in attracting swiftlets while reducing noise. Our findings highlight the critical role of sound management in swiftlet ranching. Higher loudness, especially around 80-90 dB, significantly increases swiftlet activity and maximizes daily counts. Furthermore, optimizing loudness levels, particularly at around 80 dB, extends the swiftlet presence duration, offering valuable ranching benefits. Strategic loudness management is recommended to balance attraction and noise control. Timing acoustic stimulation during mornings and late afternoons aligns with swiftlets' natural behavior. Lowering loudness to under 70 dB during midday minimizes disturbances, especially in populated areas. Weather conditions, including outdoor absolute humidity and temperature, also influence swiftlet attraction. The study finally provides guidance for complying with environmental noise regulations, demonstrating that sound levels of 70-80 dB effectively control noise. These insights support swiftlet ranching while respecting urban communities and coexisting harmoniously.